Micro habitat selection of herbivores in response to perceived predation risk and forage quality in Hluhluwe-iMfolozi game reserve - Rapp, Edvin (2017)
Predators can affect prey in many ways both through direct predation and by altering their prey’s behavior and spatial distribution. Habitat selection for prey animals is therefore a trade-off between resource availability and predation risk. This trade-off differs from species depending on for example body size, digestive system and escape tactics. In this study I looked at the effect of perceived predation risk (visibility) and forage quality (fertilization) on the selection of micro habitat for eight African herbivores. Grey duiker (Sylvicapra grimmia) and warthog (Phacochoerus africanus) both preferred plots with low visibility while impala (Aepyceros melampus) and zebra (Equus quagga) showed the opposite relationship. Elephant (Loxodonta africana), buffalo (Syncerus caffer), giraffe (Giraffa giraffe) and white rhino (Ceratotherium simum) did not respond to perceived predation risk. No species reacted to forage quality except for elephant which preferred fertilized plots. My results show that the role of perceived predation risk for micro habitat selection varies between species as well as the direction of the effect.